INHIBITORY ACTIVITIES OF ASCIDIAN Herdmania momus ON THE COLONY FORMATION OF CHINESE HAMSTER V79 CELLS, COLLECTED IN MANADO NORTH SULAWESI, INDONESIA - Sumilat, Deiske Adeliene; Wewengkang, Defny S.; Paruntu, Carolus P.; Rotinsulu, Henki (Journal of Asean Studies on Maritime Issues, 2017)
The ethanol extract of ascidian Herdmania momus collected from Manado North Sulawesi was assayed against V79, the bioassay tested to V79 cells reflects the direct action of the compounds on the cells and also is used to select active compounds for the bioassay of inflammatory cytokine production. The inhibition activity against the colony formation of Chinese hamster V79 cells showed very weak inhibited. The HPLC separation of the ethanol extract yielded two interesting fractions Fr.2.2.2 and Fr.2.2.4. were obtained from marine ascidian H. momus.Keywords: Ascidian Herdmania momus, inhibitor, North Sulawesi, V79 Cells